An Exploratory Study of Accomplished Librarian-Researchers - Kennedy, Marie R.; Brancolini, Kristine R.; Kennedy, David P. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This work explores potential factors that may contribute to a librarian becoming a highly productive researcher. An understanding of the factors can provide evidence based guidance to those at the beginning of their research careers in designing their own trajectories and to library administrators who seek to create work conditions that contribute to librarian research productivity. The current study is the first to explore the factors from the perspective of the profession’s most accomplished librarian-researchers.Methods – This exploratory and descriptive study recruited 78 academic librarians identified as highly productive researchers; 46 librarians participated in a survey about their professional training and research environments, research networks, and beliefs about the research process. Respondents supplied a recent CV which was coded to produce a research output score for the past 10 years. In addition to fixed-response questions, there were five open-ended questions about possible success factors. All data were analyzed with descriptive statistics and tests of significance correlations.Results – Accomplished librarian-researchers have professional training backgrounds and research environments that vary widely. None is statistically associated with research output. Those with densely connected networks of research colleagues who both know each other and do research together is significantly related to research output. A large group of those identified in the research networks are “both friend and colleague” and offer each other reciprocal support. In open-ended questions, respondents mentioned factors that equally span the three categories of research success: individual attributes, peers and community, and institutional structures.Conclusion – The authors found that that there are many paths to becoming an accomplished librarian-researcher and numerous factors are conducive to achieving this distinction. A positive research environment includes high institutional expectations; a variety of institutional supports for research; and extrinsic rewards, such as salary increases, tenure, promotion, and opportunities for advancement. The authors further conclude that a librarian’s research network may be an important factor in becoming an accomplished librarian-researcher. This finding is supported by both the research network analysis and responses to open-ended questions in which collaboration was a frequent theme.